Study of the Effect of RCS on Radar Detection - Haitham Kareem Ali (European Scientific Journal, ESJ, 2017)
Objectives: To study the effect of the radar cross section (RCS) area for the target on the radar operation, and to show its performance on radar detection by taking samples from the RCS. Methods/Statistical Analysis: In this paper, we tested the effect of RCS on radar detection under two features of RCS using radar lab. These features are: (i) shapes with constant area and (ii) shapes with different areas. Findings: Experimental testing of the radar delectability in order to know its capability in detecting targets under and above two features( by measuring the power of echo signal) shows that whenever the power of echo signal is high (i.e. RCS is an excellent reflector), the radar detection range is high and vice versa. Application/Improvements: This proposed approach can be used in designing the target bodies using different shapes (i.e. reflectors) to dispute the transmitted signal and to weaken it. This makes the detection of targets extremely hard.